How to Assess Agricultural Water Productivity? Looking for Water in the Agricultural Productivity and Efficiency Literature - Scheierling, Susanne M.; Treguer, David O.; Booker, James F.; Decker, Elisabeth (World Bank Group, Washington, DC, 2014)
Given population and income growth, it is widely expected that the agricultural sector will have to expand the use of water for irrigation to meet rising food demand; at the same time, the competition for water resources is growing in many regions. As a response, it is increasingly recommended that efforts should focus on improving water productivity in agriculture, and significant public and private investments are being made with this goal in mind. Yet most public communications are vague on the meaning of agricultural water productivity, and on what should be done to improve it. They also tend to emphasize water as if it were the only input that mattered. This paper presents findings from a first attempt to survey the agricultural productivity and efficiency literature with regard to the explicit inclusion of water aspects in productivity and efficiency measurements, with the aim of contributing to the discussion on how to assess and possibly improve agricultural water productivity. The focus is on studies applying single-factor productivity measures, total factor productivity indices, frontier models, and deductive models that incorporate water. A key finding is that most studies either incorporate field- and basin-level aspects but focus only on a single input (water), or they apply a multi-factor approach but do not tackle the basin level. It seems that no study on agricultural water productivity has yet presented an approach that accounts for multiple inputs and basin-level issues. However, deductive methods do provide the flexibility to overcome many of the limitations of the other methods.